Increasing Incidence of Nonalcoholic Steatohepatitis as an Indication for Liver Transplantation in Australia and New Zealand. Issue 1 (4th January 2019) - Calzadilla‐Bertot, Luis; Jeffrey, Gary P.; Jacques, Bryon; McCaughan, Geoffrey; Crawford, Michael; Angus, Peter; Jones, Robert; Gane, Edward; Munn, Stephen; Macdonald, Graeme; Fawcett, Jonathan; Wigg, Alan; et al.
Abstract : The worldwide increase in obesity and diabetes has led to predictions that nonalcoholic steatohepatitis (NASH) will become the leading indication for orthotopic liver transplantation (OLT). Data supporting this prediction from outside the United States are limited. Thus, we aimed to determine trends in the frequency of NASH among adults listed and undergoing OLT in Australia and New Zealand (ANZ) from 1994 to 2017. Data from the ANZ Liver Transplant Registry were analyzed with patients listed for fulminant liver failure, retransplantation, or multivisceral transplants excluded. Nonparametric trend, Spearman rank correlation, and regression analysis were used to assess trends in etiologies of liver disease over time. Of 5016 patient wait‐list registrants, a total of 3470 received an OLT. The percentage of patients with NASH activated for OLT increased significantly from 2.0% in 2003 to 10.9% in 2017 (trend analyses; P < 0.001). In 2017, NASH was the third leading cause of chronic liver disease (CLD) among wait‐list registrants behind chronic hepatitis C virus (HCV; 29.5%) and alcohol (16.1%). Similarly, significant increases over time in the percentage of patients undergoing OLT were observed for HCV and NASH (all trend analyses; P < 0.001) but with significant reductions in primary sclerosing cholangitis and cryptogenic cirrhosis (both P < 0.05). By 2017, NASH was the third leading cause of liver disease among patients undergoing OLT (12.4%) and behind chronic HCV (30.2%) and alcohol (18.2%). NASH also became the third most frequent etiology of CLD in patients transplanted (13.8%) with concomitant hepatocellular carcinoma by 2017. In conclusion, NASH is increasing as a primary etiology of liver disease requiring listing and liver transplantation in ANZ.